2003
DOI: 10.1289/ehp.5754
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphorus pesticide exposure of urban and suburban preschool children with organic and conventional diets.

Abstract: We assessed organophosphorus (OP) pesticide exposure from diet by biological monitoring among Seattle, Washington, preschool children. Parents kept food diaries for 3 days before urine collection, and they distinguished organic and conventional foods based on label information. Children were then classified as having consumed either organic or conventional diets based on analysis of the diary data. Residential pesticide use was also recorded for each home. We collected 24-hr urine samples from 18 children with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
163
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(176 citation statements)
references
References 10 publications
9
163
0
4
Order By: Relevance
“…First, chronic exposure from the diet is potentially very low in these rural communities. Studies in developed countries showed that children who consumed fresh fruit and related products had higher exposure levels to OP metabolites [21,22]. In our study area, children generally consume only indigenous tropical fruits with no pesticide treatment and rarely consume farmgrown fruits such as apples, oranges, and grapes.…”
Section: Discussionmentioning
confidence: 75%
“…First, chronic exposure from the diet is potentially very low in these rural communities. Studies in developed countries showed that children who consumed fresh fruit and related products had higher exposure levels to OP metabolites [21,22]. In our study area, children generally consume only indigenous tropical fruits with no pesticide treatment and rarely consume farmgrown fruits such as apples, oranges, and grapes.…”
Section: Discussionmentioning
confidence: 75%
“…Dietary intake has been identified as an important source of pesticide exposure among US children, particularly for organophosphorus (OP) and pyrethroid pesticides (Fenske et al, 2002;Clayton et al, 2003;Curl et al, 2003;Morgan et al, 2005;Lu et al, 2008aLu et al, , 2006bRiederer et al, 2008). Characterizing consumption patterns usually involves empirical and/ or probabilistic descriptions of how individuals vary with respect to the frequency and amounts of the foods they eat.…”
Section: Introductionmentioning
confidence: 99%
“…Although recent research efforts have collected much needed data to improve our understanding of the potential exposures of young children in their homes, child care centers, and other environments (Zartarian et al, 1995(Zartarian et al, , 1997(Zartarian et al, , 1998Bradman et al, 1997Bradman et al, , 2007Byrne et al, 1998;Gurunathan et al, 1998;Landrigan et al, 1999;Adgate et al, 2000Adgate et al, , 2001Fenske et al, 2000bFenske et al, , 2002Freeman et al, 2001;Lu et al, 2001;MacIntosh et al, 2001;Pang et al, 2002;Clayton et al, 2003;Curl et al, 2003;Duggan et al, 2003;Shalat et al, 2003;Wilson et al, 2003Wilson et al, , 2004Hore et al, 2005;Morgan et al, 2005;Perera et al, 2006), it is not clear what factors most influence a child's potential exposure to pesticides.…”
Section: Introductionmentioning
confidence: 99%